วาทกรรมการพัฒนา : การสร้างกระเช้าไฟฟ้าในแหล่งท่องเที่ยวจังหวัดเชียงใหม่ - ญาณิศา คำภีระ (จุฬาลงกรณ์มหาวิทยาลัย, 2005)
The objective of this research is to study discourse on development and discursive practice of government officers who respond to the project and people who lived in the area studied that would be affected by the cable car construction project for tourist attraction in Chiang Mai. This research examines. 1) How the government of officers and people gave the definition of "development" in dominant discourse 2) How people in development area and vicinity constructed their identity and signification took place 3) How and why crashing and counterattacking between alternative discursive practice and dominant discourse 4) What were the opinions of people in development area of the cable car construction project for developing sightseeing places in Chiang Mai. The results are as follows: Giving the definition of "development" on cable car construction in Chiang Mai become the conflict and meaning negotiation process between government officers who were responsible for the project and people in this community. Although the governments tried to illustrate the progress of tourism economics, the benefits in community and the increase of income from tourists by linking those concepts with the developing ideal of Chiang Mai to be "City of Life and Prosperity". Chiang Mai was set as the role model for other cities in the same region. The base of this thinking and belief were passed on to the discursive practices in the same status with dominant discourse. But the power of development could not dominates, block or press the knowledge of community development. The government development plans were challenged by several local communities actions. These actions made the counter discourse against the development because they provided the definition of development which contrasted with the belief, way of life and the environment of local community. At the same time these actions shows the untransparency of project and lack of community participation and the ideal of "Permanently development" and no emphasis on the cultural dimension. So the ideal of development preferred to present belief, holy values of life and mind. There was emphasis on value system than economic values which could make a lot of benefit but destroyed natural resources and culture of community. People in community were against the progress of technology such as cable car because they were afraid of change in their community especially culture, customs and history which could become commercialized such as a great show for tourists. The community s actions contained the efficiency campaigns and source credibility to persuade. These showed the power of history, belief, customs and culture of Chiang Mai since 700 years ago until nowadays as counter discourse on development.